Revisiting the Relationship Between Price Regulation and Pharmaceutical R&D Investment - Mujaheed Shaikh; Pietro Del Giudice; Dimitrios Kourouklis (Applied Health Economics and Health Policy, 2020)
Background: A trade-off exists between affordability of pharmaceutical products today and incentives for firms to provide new and better drugs in the future; an activity that prior studies suggest correlates with profitability, which in turn depends on price regulation. Objective In this paper we re-examined the relationship between price regulation and pharmaceutical research and development (R&D) intensity, and explored the role of profitability and cash flow in mediating this relation using the latest available data from 2000 to 2017 for the 10 most innovative pharmaceutical companies. Methods Following a framework similar to a previous study, we exploited stylized facts about sales volumes in Europe and USA, which give rise to variation in exposure to price regulation. Using ordinary least squares fixed effects models, we assess whether price regulation is related to R&D investment through cash flow effects and profitability. Results While exposure to price regulation (measured by relative market share in EU/USA) is related negatively to R&D intensity, and this result is driven by price regulation being negatively related to cash flow and profitability, the results were not significant when firm fixed effects were added to the regression models. Modeling firm dynamics showed that cash flow and profitability of European- and US-based firms responded differently to exposure to price regulation. Thus, firm specific effects play an important role in explaining the negative relationship between price regulation and R&D intensity. These results were robust to the inclusion of different time-varying firm level variables. Conclusion The findings suggest that investment decisions of firms are most likely driven by long-run inter-firm differences, and that firm effects strongly determine firm strategies in terms of R&D investment.
Keywords: 610; Pharmacoeconomics and Health Outcomes; Quality of Life Research; Health Economics; Health Administration; Public Health